Effects of Bacillus subtilis UPMB10 inoculation on growth and yield of irrigated rice grown in Semarak-Kemasin paddy soils and its clay mineralogy - Che Hassan, Nur Farhana (2017)
Rice is a main diet for half of the global human population and there is an urgent need to increase the rice yield to meet the ever-increasing demand, nationally and globally. Rice cultivation requires more potassium (K) fertilizer compared to nitrogen (N) and phosphorus (P). The challenges are due to the high cost of fertilizer-K and especially due to a majority of the soil K which presents in the insoluble form of mineral rocks and the concentrations of soil solution K are very low. Potassium solubilizing bacteria (KSB) are commonly utilized as plant growth promoters and capable to solubilize different forms of inorganic potassium and improve soil conditions, especially the microbiological and chemical properties, for increased crop production. A sequences of experiments were conducted under laboratory and field conditions with the subsequent objectives; i) to isolate and characterize the KSB from flooded rice, ii) to determine the effects of selected KSB inoculation with different fertilizer-K rates on growth and yield of rice, iii) to determine various forms of soil K concentration as affected by KSB inoculation. Twelve KSB strains were isolated from flooded rice. Four of these strains were selected for their high K solubilization activities namely RS5, RS11, RS13 and ES3, renamed UPMB22, 23, 24 and 25 respectively, along with a reference strain UPMB10, Bacillus subtilis originally isolated from oil palm (Elaeis guineensis Jacq.) roots. These five strains, especially UPMB10, were able to solubilize K in-vitro at the rates between 12.41 to 13.77 mg L-1 in 5 days of incubation and showed beneficial PGPR characteristics (N2 fixer and P solubilizer). Results from the XRD (X-Ray Diffraction) analysis showed that the soil sampled from Kemasin-Semerak Integrated Agricultural Development Project consisted of a small proportion of 2:1 clay minerals (mica) and behaved as a reservoir for soil-K, critically important to supply the short term plant-K requirements and conserve the soil-K in a long term productive crop ecosystem by reducing K loses. The clay fraction of the soil was dominated by kaolinite while the other minerals which included quartz, mica, gibbsite and magnetite occurred in minor quantities. Results from the field study indicated that inoculation with Bacillus subtilis UPMB10 significantly increased the plant height, tiller numbers and leaf chlorophyll content (SPAD). This significant increase indicates the possible beneficial effects of UPMB10 inoculation on vegetative growth of rice under irrigated system. The maximum grain yield obtained were equivalent to 8.93 and 5.94 t ha-1 with and without UPMB10 inoculation, respectively. Increased rates of K fertilization, complemented with KSB inoculation, increased grain yield production until the 80 kg ha-1 K fertilization rate; equivalent to the grain yield production with the highest rate of uninoculated fertilizer-K (120 kg ha-1). This implies that the usage of UPMB10 at 80 kg ha-1 K fertilization could save 40 kg ha-1 and yet achieve the maximum yield. The total K in soil was observed to significantly decrease after the bacterial inoculation process. The cation exchange capacity (CEC), exchangeable and water soluble K in soil did not show a significant change with UPMB10 application. CEC and water soluble K significantly increased with the application of fertilizer-K (without inoculation) until 80 kg ha-1 while the exchangeable K is significantly decreased. It indicates that 80 kg K ha-1 is sufficient for optimum rice uptake and K balance under irrigated lowland rice system. The study also showed that effective bacterial inoculation could successfully produce rice plants with improved growth and increased yield.